2021
DOI: 10.1016/j.brachy.2020.08.020
|View full text |Cite
|
Sign up to set email alerts
|

The impact of brachytherapy boost and radiotherapy treatment duration on survival in patients with vaginal cancer treated with definitive chemoradiation

Abstract: PURPOSE: Vaginal cancer is a rare tumor that is optimally treated with a combination of chemotherapy (CHT) and radiation therapy. Because of the rarity of this cancer, the benefit of a brachytherapy boost (BT) and the relevance of radiotherapy time to treatment completion (TTC) are unclear. METHODS: Patients diagnosed between 2004 and 2015 with non-metastatic vaginal cancer treated with definitive CHT and external beam radiotherapy with or without BT but with no surgery were identified in the National Cancer D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
2
3
0
Order By: Relevance
“…The radioactive implants and radioisotopes correspond to brachytherapy. We also found that beam plus implants or only implants had better effectiveness than beam radiation, similar to published studies ( 7 , 9 , 12 , 14 , 38 , 43 , 44 ). Some studies argued that image-guided brachytherapy might improve the effectiveness of brachytherapy ( 45 47 ).…”
Section: Discussionsupporting
confidence: 90%
“…The radioactive implants and radioisotopes correspond to brachytherapy. We also found that beam plus implants or only implants had better effectiveness than beam radiation, similar to published studies ( 7 , 9 , 12 , 14 , 38 , 43 , 44 ). Some studies argued that image-guided brachytherapy might improve the effectiveness of brachytherapy ( 45 47 ).…”
Section: Discussionsupporting
confidence: 90%
“…27 Another study looking at the NCDB database with patients treated with only CCRT for vaginal cancer also found that brachytherapy boost was associated with an improved 5 year overall survival (62.9% vs 49.3%, p=0.0126). 28 These findings are similar to results from large database studies in cervical cancer. [29][30][31] TECHNIQUES Brachytherapy techniques vary depending on the tumor's response and the site of the disease.…”
Section: Brachytherapysupporting
confidence: 86%
“…Patients with tumor size >5 cm had the most significant benefit from brachytherapy 27. Another study looking at the NCDB database with patients treated with only CCRT for vaginal cancer also found that brachytherapy boost was associated with an improved 5 year overall survival (62.9% vs 49.3%, p=0.0126) 28. These findings are similar to results from large database studies in cervical cancer 29–31…”
Section: Brachytherapymentioning
confidence: 53%
“…As such, although the study by Yang et al reported similar outcomes with the use of primary surgery or radiation, definitive radiation, either with or without chemotherapy, is often pursued in an attempt to avoid the toxicity associated with surgery. Within radiation treatments available, the inclusion of BT has been associated with improved outcomes in several studies [15,[21][22][23].…”
Section: Discussionmentioning
confidence: 99%